Analisis Kebijakan Antisipasi Kebocoran Radiasi dari Ruangan CT Scan di Rumah Sakit Royal Prima Medan - Rahmat Hidayatullah; Masdalina Pane; Vierto Irennius Girsang (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
The use of radiation-based medical equipment such as CT Scan poses potential risks of radiation leakage that may endanger patients, medical personnel, and the surrounding environment if not properly managed. This study aims to analyze radiation safety policies in anticipating radiation leakage in the CT Scan unit of Royal Prima General Hospital Medan, covering policy frameworks, physical protection measures, implementation challenges, and supervision and evaluation systems. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document reviews related to radiation safety policies. The results indicate that radiation safety policies at Royal Prima General Hospital Medan have referred to BAPETEN regulations and international standards, particularly in the structural protection of the CT Scan room, which has been proven effective in maintaining radiation exposure levels below the permissible limits. However, policy implementation still faces several obstacles, including budget limitations, non-compliance of some medical staff with the use of personal protective equipment, and suboptimal discipline in adhering to standard operating procedures. Supervision and evaluation have been conducted internally by certified Radiation Protection Officers and externally through periodic inspections by BAPETEN, yet further strengthening is required in terms of staff behavior and safety culture. In conclusion, radiation safety policies have been technically effective, but continuous improvement in compliance, supervision, and safety culture among medical personnel is essential to sustainably minimize the risk of radiation leakage.